Carbon absorption control model of oil palm plantation - Noryanti Nasir,; Mohd Ismail Abd Aziz,; Akbar Banitalebi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Among the largest and growing oil palm industries, Malaysia plays an important role in the world’s oil market. The contribution of the palm plantation in absorbing carbon from the atmosphere is also considerable thought, it is rarely studied. The role of the plantation in balancing carbon dioxide is significant. However, the ability of palm tree in absorbing carbon may vary within the lifespan of the plant. Therefore, managing the plantation to reach the maximum carbon dioxide absorption along with maximum oil production is challenging. This study is aimed at analyzing the carbon absorption level of the palm oil plantation. A mathematical model is proposed by considering the characteristics of palm oil trees in absorbing carbon and producing oil. It is assumed that the rate of felling can be controlled, and a system of ordinary differential equations is developed to describe the behaviour of the plantation in terms of biomass and growth rate dynamics. The resulting parameter estimation problem is solved which leads to an optimal control problem. The objective of this problem was to maximize the oil production as well as carbon absorption. Numerical simulation is illustrated to highlight the application of the proposed model.